Analysis Of Factors That Affect Students And College Student On Their Decision To Buy Products Through Online Applications In Semarang - Suryawardana, Edy; Mulyantomo, Edy; Yani, Tri Endang (Economics and Business Solutions Journal, 2019)
This study analyzes the factors that affect students and college students in online purchasing decisions in Semarang. The growth of various online companies (shops) today is like mushrooms that grow in the rainy season. The business of buying and selling goods and services online provides many benefits for consumers and online shop owners. But along with the growth of online trading, complaints from consumers also increased. This study aims to determine and analyze the influence of perceived prices, promotions and reputation on online purchasing decisions. This study uses validity and reliability test methods, classic assumption and multiple linear regression tests such as t test, f test and multiple correlation test and determination (data were processed using SPSS 24.0 software). The results obtained from this study are perceptions of price, promotion and reputation variable affect online purchasing decisions.